Analysis of the Use of Herbal Medicine in the Management of Degenerative Diseases in Medan City - Sri Lestari Ramadhani Nasution; Nada Nurjanah Afrillia; Ermi Girsang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Degenerative diseases such as coronary heart disease, diabetes, cancer, and chronic respiratory disorders represent major public health challenges in Indonesia, including in Medan City, with their prevalence continuing to rise due to modern lifestyles characterized by high intake of sugar and fat and low dietary fiber consumption. In response, herbal medicine has emerged as a popular and culturally aligned alternative treatment, particularly due to its affordability. This study aims to analyze the factors influencing the perceived effectiveness of herbal medicine in managing degenerative diseases in Medan City. A quantitative, cross-sectional design was employed, involving 369 respondents selected through stratified proportional and purposive sampling across 21 sub-districts in Medan. Data were collected using a structured, content-validated, and reliability-tested questionnaire, and analyzed using chi-square and logistic regression techniques. The majority of respondents were female (79.9%) with a secondary education level (89.7%), and most perceived the availability of herbal medicine services as adequate (93.2%). Additionally, 90% of participants considered herbal medicine effective for managing degenerative conditions. Multivariate analysis revealed that educational attainment was the most significant predictor of perceived effectiveness (p = 0.012), with those possessing higher levels of education more likely to report positive outcomes. In contrast, gender and perceived service availability did not show significant associations. These findings highlight the need to enhance health literacy through educational interventions to optimize the safe and effective use of herbal medicine. Integrating herbal medicine into the formal healthcare system and promoting collaboration between traditional and biomedical practitioners are recommended strategies for improving degenerative disease management in urban populations such as Medan. Keywords: Herbal medicine; Degenerative diseases; Gender; Education level; Service availability